Daratumumab, cyclophosphamide, bortezomib, and dexamethasone for multiple myeloma: final results of the LYRA study. Issue 10 (24th August 2022) - Yimer, Habte; Melear, Jason; Faber, Edward; Bensinger, William I.; Burke, John M.; Narang, Mohit; Stevens, Don; Gray, Kathleen S.; Lutska, Yana; Bobba, Padma; Qi, Keqin; Hoehn, Daniela; et al.
Abstract: In the primary analysis of LYRA, daratumumab + cyclophosphamide/bortezomib/dexamethasone (DARA + CyBorD) was effective and well tolerated in newly diagnosed multiple myeloma (NDMM) and relapsed multiple myeloma (RMM). We report the final analysis of LYRA (median months of follow-up: NDMM, 35.7; RMM, 35.3) after all patients completed study therapy, were followed for 36 months, or discontinued. Patients received DARA + CyBorD induction, autologous stem cell transplant (if eligible), and 12 months of daratumumab maintenance. Eighty-seven NDMM patients enrolled, 39 underwent transplant, and 63 completed maintenance. Rates of complete response or better were 48.7% and 29.8% for NDMM transplant and NDMM non-transplant patients, respectively, and 36-month progression-free survival rates were 69.3% and 72.6%. Grade 3/4 treatment-emergent adverse events occurred in 61.6% of NDMM patients. Efficacy and safety data are also reported for the smaller RMM cohort ( n  = 14). DARA + CyBorD followed by daratumumab maintenance was well tolerated and achieved deep, durable responses in NDMM and RMM.